A randomized pilot study to investigate the effect of opioids on immunomarkers using gene expression profiling during surgery. Issue 12 (December 2019) - Wodehouse, Theresa; Demopoulos, Mary; Petty, Robert; Miraki-Moud, Farideh; Belhaj, Alla; Husband, Michael; Fulton, Laura; Randive, Nilesh; Oksche, Alexander; Mehta, Vivek; Gribben, John; Langford, Richard
Abstract : Abstract: Endogenous opioid peptides and exogenous opioids modulate immune function, and animal and human studies have shown that some have a depressant immunomodulatory effect. This is potentially of high clinical significance, eg, in cancer patients and surgery. The primary objective of this pilot study was to evaluate the effect of morphine and oxycodone on immune pathways associated with immunosuppression in gynecological laparotomy patients. Gene expression was analyzed in CD4 +, CD8 +, and natural killer (NK) cells using the 3′ Affymetrix microarray. Patients were randomized to receive morphine, oxycodone, or nonopioid "control" analgesia during and after surgery. Genes demonstrating differential expression were those with a ≥±2-fold difference and P -value ⩽0.05 after analysis of variance. Cytometric bead array and NK cell degranulation assay were used to investigate changes in serum cytokine concentration and in NK cell cytotoxicity, respectively. Forty patients had satisfactory RNA which was hybridized to gene chips. Genes were identified (Partek Genomics Suite 6.6) at baseline, 2, 6, and 24 hours and were either ≥2-fold upregulated or downregulated from baseline. At 2 hours, a large number of genes were downregulated with morphine but not with control analgesia or oxycodone. Statistically significant increases in IL-6 concentrations were induced by morphine only; NK cell activity was suppressed with morphine, but maintained with oxycodone and epidural analgesia. Gene expression profiles suggest that at 2 hours, post incision morphine appeared to be immunosuppressive as compared to oxycodone and nonopioid control analgesia. Abstract : Pilot study evaluating the effects of morphine and oxycodone on immunosuppression pathways in noncancer surgery. Two-hour postincision morphine appears to be immunosuppressive compared with oxycodone.